2021
DOI: 10.1002/esp.5270
|View full text |Cite
|
Sign up to set email alerts
|

Artificial bifurcation effect on downstream channel dynamics of a large lowland river, the Atchafalaya

Abstract: Artificial river bifurcations have been widely created for different purposes. Yet, long‐term dynamics in the bifurcated channels and natural channels downstream of the artificial bifurcation nodes are not well investigated. Herein, we employed an approach combining three decades (1977–2006) of bathymetric survey records, geographic information system (GIS) application, and bed material transport modeling to investigate riverbed dynamics in an artificially bifurcated channel and the downstream natural channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…While originally designed to transport 30% of the Atchafalaya River streamflow, the channel has rapidly evolved (Fisk, 1952;Roberts, 1998). Using historic hydrographic surveys over about a 30-year period, from 1977 to 2006, Tang et al (2022) found that Wax Lake Outflow Channel now transports 41% of Atchafalaya River discharge but 52% of its bedload.…”
Section: Channel Engineering and Fluvial Responsementioning
confidence: 99%
See 2 more Smart Citations
“…While originally designed to transport 30% of the Atchafalaya River streamflow, the channel has rapidly evolved (Fisk, 1952;Roberts, 1998). Using historic hydrographic surveys over about a 30-year period, from 1977 to 2006, Tang et al (2022) found that Wax Lake Outflow Channel now transports 41% of Atchafalaya River discharge but 52% of its bedload.…”
Section: Channel Engineering and Fluvial Responsementioning
confidence: 99%
“…While originally designed to transport 30% of the Atchafalaya River streamflow, the channel has rapidly evolved (Fisk, 1952; Roberts, 1998). Using historic hydrographic surveys over about a 30‐year period, from 1977 to 2006, Tang et al (2022) found that Wax Lake Outflow Channel now transports 41% of Atchafalaya River discharge but 52% of its bedload. Interestingly, while the artificially created Wax Lake Outlet channel is degrading and increasing in size the natural Atchafalaya River mainstem outlet channel is aggrading.…”
Section: Channel Engineering and Fluvial Responsementioning
confidence: 99%
See 1 more Smart Citation